Competencies of oncology nurses in Malaysia - Maskor, Nor Aida; Nik Mahmood, Nik Hasnaa; Mohd Anuar, Mohd Ashraff (Universiti Putra Malaysia, 2009)
Oncology nurses are considered the most important individuals in support of the treatment of cancer patients. Several studies have indicated that these nurses require an array of competencies, yet little attention has been paid to understanding such competencies in non-Western settings. This paper discusses preliminary findings of a study conducted to identify the competencies of oncology nurses in Malaysian hospitals. A qualitative research method was used for the purposes. Ten oncology nurses from a public hospital in Kuala Lumpur participated in two focus groups interview. The results revealed that oncology nurses should possess among others, personal, interpersonal and technical competencies including knowledge on treatment options, working with recurrence, chances of cure, impact of the disease on family members, communications and counseling skills as well as a heightened cultural and religious sensitivity.